P81 Looking after the mad, bad and sad: psychiatry simulations. (31st December 2017) - Merriman, Clair; McDonald, Rozz; Butler, Clare
Abstract : Background: 1 in 4 experience a mental health problem per year, with a 25 year reduced life expectancy in those with the most severe mental illnesses. Despite the drive to put physical and mental health on equal footing, Psychiatry teaching to non-Psychiatric colleagues is still woefully under-developed leading to trainees who are unequipped in assessing and managing such zpatients in acute hospital settings. This has overall implications on patient safety and care. Simulation Aims: * To assess a patient with a psychiatric illness including performing a mental state examination * To utilise communication skills and recognise these are transferrable to psychiatric patients * To discuss management plans appropriate to an FY1/FY2 at the start of their year * To reflect on the challenges that interactions with psychiatric patients may pose, and how this could be replicated in other scenarios dealing with those without mental health issues * To adopt learning strategies to manage these challenges to facilitate improved outcomes next time. Project Description: 36 FY1s were timetabled to participate over two dates. FY1s divided into 3 simulations with actors and facilitators: 1. Assessing capacity in depressed patient 2. Managing the agitated delirious patient 3. Managing the antisocial patient demanding methadone Each simulation had specific learning outcomes for communication skills and clinical knowledge. Plenary session concluded main clinical and communication learning points, with shared peer learning outcomes and reflections on similar situations on the wards. Facilitators were Psychiatric, Medical and Nursing colleagues, enhancing inter-professional learning. Outcomes: Pre and post course confidence questionnaire using 1–10 likert scale was administered. Seven questions were posed covering the sessions' aims. White space text for identifying three learning points and further scenarios they wish to observe. Provisional results from the first session demonstrated a mean increased confidence in all areas measured, with mean score ranges of 1.0–3.6. Largest confidence increase was seen in prescribing methadone and managing the acutely agitated and disturbed patient. Qualitative data echoed largest learning areas were in managing opiate withdrawal, prescribing methadone and assessing and managing delirium. Conclusions and Recommendations: Overall results following the delivery of the second session will provide a clearer description of whether the specified learning outcomes were obtained. Current faculty simulation members who observed suggested scenarios will be suitable for other trainee grades and professionals. Scenarios have therefore been proposed to simulation lead at Trust for further development of this pilot project.